Economic Impact Analysis of Load Shifting in a Smart Household - Farzambehboudi, Yasaman; Erdinc, Ozan; Boynuegri, Ali Rifat; Ucun, Levent; Oz, Muhammed Ali (IEEE, 2018)
The global energy consumption has been showing a remarkable growth particularly in the last two decades in parallel to the arising environmental concerns. In consequence of researching alternative solutions to ensure a more sustainable end environmental friendly energy issue, the smart grid vision has emerged. The demand side participation through demand response (DR) strategies plays a crucial role in the smart grid concept. This paper presents a pricing based DR scheme oriented simulation study of an experimental smart home, which is located in Yildiz Technical University in Istanbul, Turkey. All types of controllable and non-controllable household electric appliances are modeled in MATLAB/Simulink (R) by using data from real measurements. In order to provide an energy management concept, an optimization algorithm is developed to minimize electricity bills and reduce peak load demand by controlling the shiftable loads.
Keywords: Economic impact analysis; energy management; load shifting; smart household; OPTIMIZATION; MANAGEMENT; Computer Science; Energy & Fuels